STEM Learning Model Implementation Assisted by E-Module on Problem Solving and Mathematical Literacy Abilities (International Journal of Scientific Research and Management (IJSRM), 2025)
This research aims to analyze the effect of STEM model learning on problem-solving ability and mathematical literacy ability. The research uses a quantitative approach with a Quasi-Experimental research design in the form of a Pre-Post Group Design. The research instruments are learning instruments, tests, interviews, and test question validation questionnaires. The data analysis results using the Wilcoxon test show that there is an influence of using the STEM learning model on problem-solving abilities and mathematical literacy with a p-value lower than 0.05. The STEM learning model improves the students’ problem-solving abilities in the medium category (N-Gain = 0.4644) and mathematical literacy abilities in the medium category (N-Gain = 0.3889). These results conclude that the STEM learning model can be an alternative solution to improving students’ problem-solving abilities and mathematical literacy.